Objects as human bodies: cross-linguistic colexifications between words for body parts and objects - Tjuka Annika (Linguistic Typology)
Many languages have words that denote a human body part and an object, for example, hand, which refers to a part of a person and a watch. As of yet, there is no systematic study on the distribution of these shared names, i.e., colexifications, between two concrete semantic domains in a variety of languages. Here, I present a study that investigates colexifications between body and object concepts, i.e., body-object colexifications. By using a newly established workflow, colexifications are automatically extracted based on a seed list containing 134 body concepts and 650 object concepts. The analysis focuses on the frequency, distribution, cognitive relations, and coincidental cases of 78 body-object colexifications occurring across 396 language varieties. The results show that some body-object colexifications are widespread, but most occur in a small number of language varieties. By creating a network structure to examine individual relations and additionally comparing ratings of visual and haptic perception across concepts, the study indicates that the similarity of visual perception plays a central role in the emergence of body-object colexifications. The findings provide a first general overview of the phenomenon and offer ample opportunities for future research.